Place branding of an innovation cluster : Case: Greater Helsinki region from a start-up’s perspective - Nikulin, Antti (My University, 2022)
Places compete with each other over many things these including businesses. For differentiating themselves from the others and appearing more attractive to different stakeholders, places have started to brand themselves. At the same time, to facilitate innovation, businesses have increasingly begun to cluster to certain places which Silicon Valley is a famous example of. Regions have recognized this and its value to the local economy, and are invested in providing the required setting to support this kind of development. This thesis intends to discover what kind of a place brand Greater Helsinki region has as an innovation cluster from start-ups’ perspective. The study examines which factors are valued by start-ups and what kind of a brand identity and value proposition the region is perceived to have. The study was conducted by applying the methods of case study and semi-structured theme interviews. In total, nine people representing eight different organizations were interviewed with six of these organizations being start-ups and the remaining two promoting the region and one of its clusters. Thematic analysis was applied to interpret the data. The results indicate that Greater Helsinki region’s core competence is in smart and clean innovation, health-based solutions, and in gaming. In these fields, the region is seen as an attractive and globally competitive location. Values that describe the region and also Finland are trust, open-minded, safety, and openness. Helsinki is an ideal place for piloting and testing, and serves as a gateway to European markets between East and West.

Paikat kilpailevat keskenään monista asioista, kuten yrityksistä. Erottautuakseen muista ja esiintyäkseen houkuttelevampina vaihtoehtoina eri sidosryhmille, paikat ovat alkaneet brändätä itseään. Samaan aikaan, edistääkseen innovointia, yritykset ovat lisääntyvissä määrin alkaneet keskittyä tiettyihin paikkoihin, joista Piilaakso on kuuluisin esimerkki. Alueet ovat tunnistaneet tämän kehityssuunnan ja sen merkityksen paikalliselle taloudelle ja ovat ryhtyneet tarjoamaan vaadittuja puitteita tukeakseen tämän suuntaista kehitystä. Tämä tutkielma pyrkii selvittämään, millainen paikkabrändi pääkaupunkiseudulla innovaatioklusterina on startup-yritysten näkökulmasta. Tutkielma tarkastelee, mitä tekijöitä startup-yritykset arvostavat sekä millainen brändi-identiteetti ja arvolupaus alueella koetaan olevan. Tutkielma toteutettiin hyödyntämällä case-tutkimusta ja puolistrukturoituja teemahaastatteluja tutkimusmenetelminä. Tutkielmaa varten haastateltiin yhteensä yhdeksää henkilöä kahdeksasta eri organisaatiosta, joista kuusi oli startup-yrityksiä ja kaksi muuta aluetta sekä sen klustereita edustavia tahoja. Tulosten analysoinnissa hyödynnettiin temaattista analyysiä. Tulokset osoittavat pääkaupunkiseudun ydinosaamisen olevan ympäristön puhtautta edistävissä innovaatioissa, terveysratkaisuissa ja peliteollisuudessa. Aluetta pidetään näille aloille houkuttelevana ja kansainvälisesti kilpailukykyisenä sijaintina. Pääkaupunkiseutua ja samalla Suomea kuvaavia arvoja ovat luottamus, avarakatseisuus, turvallisuus ja avoimuus. Helsinki on ihanteellinen paikka pilotointiin ja testaamiseen, sekä toimii väylänä Euroopan markkinoille idän ja lännen välissä.
Keywords: Place branding, innovation cluster, economic geography, Greater Helsinki, start-up, paikkabrändäys, innovaatioklusteri, talousmaantiede, Helsingin seutu, startup